2020
DOI: 10.1371/journal.pone.0239613
|View full text |Cite|
|
Sign up to set email alerts
|

Associations between individual variations in visual attention at 9 months and behavioral competencies at 18 months in rural Malawi

Abstract: Theoretical and empirical considerations suggest that individual differences in infant visual attention correlate with variations in cognitive skills later in childhood. Here we tested this hypothesis in infants from rural Malawi (n = 198-377, depending on analysis), who were assessed with eye tracking tests of visual orienting, anticipatory looks, and attention to faces at 9 months, and more conventional tests of cognitive control (A-not-B), motor, language, and socioemotional development at 18 months. The re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…20 Visual orienting testing in infants has benefited from the replacement of manual methods of eye movement coding with more automated methods of eye-tracking that use remote infrared light sources and cameras. 21 22 The majority of studies examining infant visual orienting by automated eye-tracking come from high-resource laboratories in Western countries, but similar research has recently been expanded to assess visual orienting [23][24][25][26] as well as other aspects of cognition in children in less studied populations in mid-income and low-income countries. [27][28][29] These studies have shown that eyetracking can be performed in low-resource settings, typically at central healthcare facilities, [26][27][28] although the use of a portable system at participants' homes in rural Vanuatu has also been reported.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…20 Visual orienting testing in infants has benefited from the replacement of manual methods of eye movement coding with more automated methods of eye-tracking that use remote infrared light sources and cameras. 21 22 The majority of studies examining infant visual orienting by automated eye-tracking come from high-resource laboratories in Western countries, but similar research has recently been expanded to assess visual orienting [23][24][25][26] as well as other aspects of cognition in children in less studied populations in mid-income and low-income countries. [27][28][29] These studies have shown that eyetracking can be performed in low-resource settings, typically at central healthcare facilities, [26][27][28] although the use of a portable system at participants' homes in rural Vanuatu has also been reported.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…From the assumption that attention in infancy is linked to the development of self-regulation, researchers have developed several attention indices based on behavioral observations and measures. Commonly used measures include dwelling time (Papageorgiou et al, 2015), looking duration (Kraybill et al, 2019; Rose et al, 2012), anticipatory looks (Holmboe et al, 2018; Pyykkö et al, 2020), visual disengagement (Geeraerts et al, 2019; Holmboe et al, 2018), or looking behavior in play contexts (Brandes-Aitken et al, 2019; Johansson et al, 2016). Indeed, due to the immature motor and verbal skills of infants, studies investigating attentional control in infants have heavily relied on various measures of looking behavior (Bornstein, 1985; Colombo et al, 1991; Colombo & Mitchell, 2009; Gredebäck et al, 2010; Oakes, 2010, 2012).…”
Section: Attentional Control In Infancymentioning
confidence: 99%
“…Although used as measures of attentional control, neither anticipatory looking behavior nor voluntary disengagement in the first year are associated with self-regulatory functions in infancy (Holmboe et al, 2018) nor later in toddlerhood (Geeraerts et al, 2019; Nakagawa & Sukigara, 2013; Pyykkö et al, 2020). Sustained attention, on the other hand, is associated with effortful control at both 22 months (Kochanska et al, 2000) and 2 years (Johansson et al, 2015), but not at 14 or 33 months (Kochanska et al, 2000).…”
Section: Attentional Control In Infancymentioning
confidence: 99%
See 1 more Smart Citation